In vitro and in silico analysis of Galanthine from Zephyranthes carinata as an inhibitor of acetylcholinesterase (2022)
ABSTRACT: Zephyranthes carinata Herb., a specie of the Amaryllidoideae subfamily, has been reported to have inhibitory activity against acetylcholinesterase. However, scientific evidence related to their bioactive alkaloids has been lacking. Thus, this study describes the isolation of the alkaloids of this plant, and their inhibition of the enzymes acetylcholinesterase (eeAChE) and butyrylcholinesterase (eqBuChE), being galanthine the main component. Additionally, haemanthamine, hamayne, lycoramine, lycorine, tazettine, trisphaeridine and vittatine/crinine were also isolated. The results showed that galanthine has significant activity at low micromolar concentrations for eeAChE (IC50 = 1.96 μg/mL). The in-silico study allowed to establish at a molecular level the high affinity and the way galanthine interacts with the active site of the TcAChE enzyme, information that corroborates the result of the experimental IC50. However, according to molecular dynamics (MD) analysis, it is also suggested that galanthine presents a different inhibition mode that the one observed for galanthamine, by presenting interaction with peripheral anionic binding site of the enzyme, which prevents the entrance and exit of molecules from the active site. Thus, in vitro screening assays plus rapid computer development play an essential role in the search for new cholinesterase inhibitors by identifying unknown bio-interactions between bioactive compounds and biological targets.